1999
DOI: 10.1074/jbc.274.11.7557
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Features Underlying the Sequential Phosphorylation of HS1 Protein and Its Association with c-Fgr Protein-tyrosine Kinase

Abstract: The hematopoietic lineage cell-specific protein HS1 was shown to undergo a process of sequential phosphorylation both in vitro and in vivo, which is synergistically mediated by Syk and Src family protein-tyrosine kinases and essential for B cell antigen receptor-mediated apoptosis. We have now identified tyrosine 222 as the HS1 residue phosphorylated by the Src family protein kinases c-Fgr and Lyn, and we show that a truncated form of HS1 (HS1-208-401) lacking the N-terminal putative DNA binding region and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 31 publications
0
69
0
Order By: Relevance
“…Other studies have confirmed the association of Lyn with the Epo receptor and its participation in downstream signaling, including phosphorylation of STAT5 (Chin et al, 1998;Arai et al, 2001). Lyn is also activated by Epo in CD34 þ cells maturing along the erythroid lineage (Harashima et al, 2002), and can phosphorylate protein Band 3 in erythrocytes (Brunati et al, 2000).…”
Section: Introductionmentioning
confidence: 84%
“…Other studies have confirmed the association of Lyn with the Epo receptor and its participation in downstream signaling, including phosphorylation of STAT5 (Chin et al, 1998;Arai et al, 2001). Lyn is also activated by Epo in CD34 þ cells maturing along the erythroid lineage (Harashima et al, 2002), and can phosphorylate protein Band 3 in erythrocytes (Brunati et al, 2000).…”
Section: Introductionmentioning
confidence: 84%
“…In detail, the HS1 sites Y 378 and Y 397 are phosphorylated by Syk in vitro [36] and presumably by ZAP70 upon TCR ligation [27]. Besides these tyrosine motifs, in vitro phosphorylation of Y 222 (YKKT) [36][37][38] and Y 198 (YGIQ) [39] was documented. However, since the sequence of these phospho-sites pretty much differs from the Nck SH2 consensus-binding sequence, an interaction with the Nck SH2 domain is rather unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…HS1 di ers from cortactin in that it contains only three complete cortactin repeats ( Figure 1), and that the helical and proline-rich domains are inverted with respect to cortactin . In spite of these di erences, HS1 shares functional similarities with cortactin, serving as a Srcfamily tyrosine kinase substrate (Takemoto et al, 1995;Brunati et al, 1999) as well as playing a unique and essential role in antigen-receptor induced B cell clonal expansion .…”
Section: Structural Organization Of Cortactin and Related Proteinsmentioning
confidence: 99%